Energy Planning Policies with Environmental Considerations : Case Study Egypt (Cairo University.Faculty of Engineering, 1995)
The last decade has witnessed a fundamental change in the planning process for development. It is now recognized that the dimension of environment protection is of vital importance for sustainable development. From the comparative survey of available energy planning models, it was found that the environmental considerations are limited only to estimating the pollution load, thus sending false price signals to the technology market, and leading to environmentally distorted policy decisions. The centrepiece of this research is a methodology for integrated energy sector planning, policy impact assessment, and policy mix analysis, incorporating the impact of environmental externality cost of energy supply and use into the planning process. The model aims at determining the least cost energy planning policy path for a country, namely Egypt, with the least environmental damage.